GOTONG ROYONG LALAWATANPADA TRADISI HAUL MASYARAKAT BANJAR PAHULUAN DESA ANDHIKA SEBAGAI SUMBER PEMBELAJARAN IPS - Gazali Rahman (Universitas Lambung Mangkurat, 2017)
Haul tradition for remember person had been deed in Andhika Village. Still continued until now. Village peoples working together be successfullythat religious ceremony. However we claimed many problems out of order goes on village peoples working togetherness. In the global era was needed speed rhythm and profesionalism. In the early, that was grew up catering industries and instant noodles sold on regencyc capital city market. Working togetherness called lalawatan depend on many factors attack.Village peoples working togetherness values in lalawatan areentrenchment or legacy making it still exist. The values is the heritage for the young generation. Not much more if the lalawatan values can be IPS learning sources..Keywords:Haul tradition, togetherness, and IPS learning sources Tradisi Haul untuk mengenang seseorang yang telah meninggal dunia di Desa Andhika terus berlangsung hingga kini. Warga desa bergotong royong demi mensukseskan upacara keagamaan tersebut. Walaupun diakui ada beberapa kendala yang menggerus atau mengurangi peran pegotongroyong lalawatan. Era globalisasi yang menghendaki kecepatan dan pofesionalisme, mulai tumbuhnya industri katering dan bumbu masak instant yang marak dijual di pasar ibukota kabupaten. Gotong royong lalawatan tetap bertahan dalam “gempuran” faktor-faktor tadi. Nilai-nilai yang tderkandung dalam gotong royong lalawatan adalah benteng yang membuat kegiatan bersama warga itu tetap ada. Nilai-nilai yang dapat diangkat dean diwariskan kepada generasi muda. Jaddfi tidak berlebihan bila nilai-nilai kegotongroyongan lalawatan dapat menjadi sumber pembelajaran IPS.Kata kunci: tradisi haul, kebersamaan, dan sumber belajar IPS